Impediments to Tenure for Female Assistant Professors. ASHE Annual Meeting Paper Susan Kolker Finkel and Steven G. Olswang. - Finkel, Susan Kolker (Distributed by ERIC Clearinghouse, 1994)
In an effort to understand the persistent lack of representation of females in senior ranks at top research universities this study examined the attitudes of female assistant professors toward 14 possible impediments to their gaining tenure. Subjects were tenure-track assistant professors in a large, public research university where women are found less frequently in the senior ranks and more often in junior ranks. Of 189 surveys distributed, 124 were returned (66 percent return rate). Over 44 percent of participants had no children and 49 percent acknowledged that they had postponed having a child. Results revealed that child rearing most significantly affects women's chances to gain tenure with over 40 percent of respondents reporting that "time required by children" is a serious impediment to receiving tenure. These results were even more significant for women with children 5 years old or younger, 80 percent of whom reported that time with children was a serious impediment to obtaining tenure. A large number of women reported that they plan to remain childless because of their careers. The majority of female assistant professors who have postponed or decided not to have children reported that they are less satisfied with their work. Sexual harassment and sexism were perceived by fewer respondents as serious impediments to obtaining tenure. The report proposes greater flexibility in the timing of the tenure decision. (Contains 28 references.) (JB)